Properties of Nanocrystals-formulated Aluminosilicate Bricks - Francesca Conciauro; Emanuela Filippo; Claudia Carlucci; Viviana Vergaro; Francesca Baldassarre; Rosaria D’Amato; Gaetano Terranova; Caterina Lorusso; Paolo Maria Congedo; Barbara Federica Scremin; Giuseppe Ciccarella (Nanomaterials and Nanotechnology)
n the present work, seven different types of nanocrystals were studied as additives in the formulation of aluminosili‐ cate bricks. The considered nanocrystals consisted of anatase titanium dioxide (two differently shaped types), boron modified anatase, calcium carbonate (in calcite phase), aluminium hydroxide and silicon carbide (of two diverse sizes), which were prepared using different methods. Syntheses aim to give a good control over a particle’s size and shape. Anatase titania nanocrystals, together with the nano-aluminium hydroxide ones, were synthesized via microwave-assisted procedures, with the use of different additives and without the final calcination steps. The silicon carbide nanoparticles were prepared via laser pyrolysis. The nano-calcium carbonate was prepared via a spray drying technique. All of the nanocrystals were tested as fillers (in 0.5, 1 and 2 wt. % amounts) in a commer‐ cial aluminosilicate refractory (55 % Al2O3, 42 % SiO2). They were used to prepare bricks that were thermally treated at 1300 °C for 24 hours, according to the international norms. The differently synthesized nanocrystals were added for the preparation of the bricks, with the aim to improve their heat- insulating and/or mechanical properties. The nanocrystals- modified refractories showed variations in properties, with respect to the untreated aluminosilicate reference in heat- insulating performances (thermal diffusivities were measured by the “hot disk” technique). In general, they also showed improvements in mechanical compression resist‐ ance for all of the samples at 2 wt. %. The best heat insula‐ tion was obtained with the addition of nano-aluminium hydroxide at 2 wt. %, while the highest mechanical compres‐ sion breaking resistance was found with nano-CaCO3 at 2 wt. %. These outcomes were investigated with complemen‐ tary techniques, like mercury porosimetry for porosity, and Archimedes methods to measure physical properties like the bulk and apparent densities, apparent porosities and water absorption. The results show that the nano-alumini‐ um hydroxide modified bricks were the most porous, which could explain the best heat-insulating performances. There is a less straightforward explanation for the mechanical resistance results, as they may have relations with the characteristics of the pores. Furthermore, the nanoparti‐ cles may have possible reactions with the matrix during the heat treatments.